Od Vodnikovega "kramljanja z ljudstvom" do načela obrnjene piramide - Kalin Golob, Monika (Javnost (Ljubljana), 2008)
The article attempts to determine the beginnings of an independent journalistic style in the Slovene language by means of a textual-stylistic analysis of the news in Vodnik's paper Lublanske novice (1797-1800) and first Slovenian daily newspaper Slovenski narod (1868-1945). Lublanske novice still lacked of a specialised language tools, which would provide evidence of the development of reporting as a specific linguistic subgenre. Thus Vodnik cannot be considered the founder of the journalistic style which was only formed during the last three decades of the 19th century, when a completely new function started to emerge in the language of daily newspapers. In that period stylistic particularities developed that led to the development of a specific journalistic discourse in reporting, most evidently in the news.
Keywords: Slovenia; Slovenija; časniki; journalism; novinarstvo; Ljubljanske novice (periodična publikacija); 1797/1800; obveščanje; informiranje; poročanje; Slovene; slovenščina; stil; stilistika; stylistics